A Group Level Analysis of Self-evaluations Associated with Cognitive Load - Alexios Kouzalis (Peoples' Friendship University of Russia (RUDN University), 2023)
Self-evaluation, or self-rating, is the process by which people evaluate themselves with the purpose of improving several aspects of their personalities or skills and it is closely related to the cognitive function of metacognition. The purpose of the study was to investigate the degree of implication of various brain areas to meta-cognition as it relates to subjective ratings of cognitive effort when performing mathematical problems of different complexity. To achieve this, participants were recruited to solve mathematical problems (addition, subtraction, multiplication, and division) in three levels of difficulty, while inside an fMRI scanner. After solving a given task, they were asked to evaluate the amount of effort they spent to solve it. Brain signal was collected during their answers, which was then analyzed with the aid of computer software. Results of the analysis show that increases in task difficulty activate the frontal lobe, cingulate and insular cortex areas. The parietal lobule, the precuneus and the cingulate gyrus were found to be active as well as during all four mathematical operations.